The Effect of Motivation on Professional Construction Workforce Commitment and Project Performance - Yanti Yanti; Manlian Ronald A; Hendrik Sulistio (Jurnal Indonesia Sosial Teknologi, 2024)
The phenomenon of good project performance in East Kalimantan needs to be aware of the possibility of project labor turnover. Employee commitment serves as a stabilizing force that maintains the direction of behavior even if the company fails to meet expectations. Employee commitment is a psychological condition that creates a personal attachment to an organization. This study aims to identify the influence of Motivation on Professional Construction Labor Commitment and Project Performance. This study uses an Explanatory Sequential Mixed Method design, involving 250 respondents of employees and staff of contractor companies, consultants, and building project owners, with SmartPLS SEM analysis at the quantitative stage. The qualitative stage involves the leaders of contractor companies, consultants, and building project owners. The results of the study show that Motivation has a significant effect on the Commitment of Professional Construction Workforce.